Pengaruh Lama Fermentasi Menggunakan Mikroba Ghalkoff terhadap Perubahan Konsentrasi Kandungan Kafein Kopi Robusta Organik Kabupaten Lampung Barat - Wijaya, Riky Yan; Tamrin, Tamrin; Sugianti, Cicih (Jurnal Agricultural Biosystem Engineering, 2023)
Coffee is a beverage ingredient not only famous in Indonesia but also famous throughout the world. Caffeine is the most important compound found in coffee, caffeine functions as an element of taste and aroma in coffee beans. Excessive acid and caffeine content in coffee can have an impact on health. This study aims to determine the effect of fermentation time using microbial Ghalkoff on changes in concentration of caffeine, protein and acidity content in organic robusta coffee without reducing the taste of coffee. This research was conducted from July to August 2018 at PT. Ghaly Roelies Indonesia, Kecamatan Kemiling, Bandar Lampung. This study uses a laboratory and Kruskal-Wallis test Non-parametric statistical test based on questionnaire test on the level of preference. The results showed the effect of changes in the concentration of caffeine, protein and acidity levels in organic robusta coffee with control of the initial data resulting in a decrease in the concentration of caffeine by 27%. While the results of the N-Rank organoleptic test with Kruskal-WallisTest showed that administering long-acting organic coffee fermentation using microbial ghalkoff can increase the preference for coffee flavor, aroma and color. Keywords: Caffeine, Fermentation, Kruskal-Wallis Test, Organic Robusta Coffee.